Family research and demographic analysis: new insights from the German Family Demography Panel Study (FReDA) - Bujard, Martin; Hank, Karsten; Pollak, Reinhard (Comparative population studies, 2023)
This is the Editorial on the Special Issue "Family Research and Demographic Analysis – New Insights from the German Family Demography Panel Study (FReDA)".
Keywords: Aufsatz in Zeitschrift